Analysis of Flat Slabs Strengthened by Reinforced Concrete Overlays - Čereš, Daniel; Gajdošová, Katarína (Vysoké učení technické v Brně,Fakulta stavební, 2024)
The strengthening of flat concrete slabs using reinforced concrete overlays is an efficient method of increasing both the flexural stiffness and punching shear capacity of such slabs. The interface between the two concrete layers transmits a large amount of stress, so detailing of the interface is crucial to achieve an increase in resistance. The analysis introduced below compares the efficiency of different amount of shear studs and the effect of the dimensions of the overlaid concrete on punching shear capacity.
Keywords: Punching shear capacity; flat slab; concrete overlay; shear studs